Enhancing Sow and Piglet Performance: Evaluation of a Probiotic Additive of Saccharomyces boulardii RC009 from Late Gestation through Lactation - Corti Isgro, Maite (2024)
Nursery is a critical point in farms, involving piglets survival and growth. This study aimedto evaluate Saccharomyces cerevisiae var. boulardii RC009 (Sb) as a nutritional feed additiveto sows and their piglets during late gestation and lactation in their productiveperformance. The study was conducted in three groups of 12 sows. One group receivedthe basal diet, and the other two received a food additive of Sb during the last three weeksof gestation and all-over lactation. In the creep feeding, litter from one of the treated sowgroups was administered with the same yeast food additive. Sows that received theadditive had a significantly (P<0.05) shorter farrowing, a lower percentage of piglets withlow birth weight, and less variation in birth weight. Litters from sows that consume theprobiotic had a significantly (P<0.05) higher weight at 20 days old (5610.78±1178.1g), incomparison with litters that also consume the probiotic in the creep feeding(5270.58±999.42g) and litters from no treated sows (5079.46 ±1178.37g). Litters from thesows that did not consume the probiotic had a higher mortality rate (13.68%) duringnursery as compared to litters (10, 11%, and 11.56%) from treated sows. It was concludedthat the use of a probiotic additive of Saccharomyces boulardii RC009 in the last threeweeks of gestation and during nursing had a positive impact on farrowing duration andlitter performance. However, the combined administration of yeast in the sow´s diet andpiglet creep feeding requires more accurate studies.